2021
DOI: 10.1155/2021/8037459
|View full text |Cite|
|
Sign up to set email alerts
|

A Clinical Study of the Effect of Estradiol Valerate on Sleep Disorders, Negative Emotions, and Quality of Life in Perimenopausal Women

Abstract: In this prospective study, we randomly divided 100 patients with perimenopausal syndrome equally into the control group (n = 50) receiving conventional treatment and the study group (n = 50) receiving estradiol valerate. The indicators observed were endometrial thickness, uterine volume, and the levels of LH (luteinizing hormone), FSH (follicle-stimulating hormone), and E2 (estradiol) of the patients before and after treatment. The Pittsburgh Sleep Quality Index (PSQI), Hamilton Anxiety/Depression Scale (HAMA/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Correlation analysis of reproductive hormone levels with sleep indicators assessed objectively and subjectively showed that the faster the FSH changed, the longer the sleep duration, and the poorer the sleep quality all were associated with poorer self-reported PSQI [33]. Estradiol valerate has been shown to improve serum sex hormone levels, sleep disturbances, negative mood and quality of life in patients with perimenopausal syndrome [34]. In this study, melatonin treatment significantly improved the FSH, LH and E2 levels in patients with perimenopausal sleep disorders, but had no significant effect on P, T and PRL.…”
Section: Discussionmentioning
confidence: 99%
“…Correlation analysis of reproductive hormone levels with sleep indicators assessed objectively and subjectively showed that the faster the FSH changed, the longer the sleep duration, and the poorer the sleep quality all were associated with poorer self-reported PSQI [33]. Estradiol valerate has been shown to improve serum sex hormone levels, sleep disturbances, negative mood and quality of life in patients with perimenopausal syndrome [34]. In this study, melatonin treatment significantly improved the FSH, LH and E2 levels in patients with perimenopausal sleep disorders, but had no significant effect on P, T and PRL.…”
Section: Discussionmentioning
confidence: 99%
“…This article has been retracted by Hindawi, as publisher, following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of systematic manipulation of the publication and peer-review process.…”
mentioning
confidence: 99%